THE ROLE OF ACCOUNTING APPLICATIONS IN ENHANCING TRANSACTION GROWTH IN ISLAMIC BANKING IN THE MODERN ERA - Syarif, Siti Alwya (Cattleya Darmaya Fortuna, 2024)
The rapid advancement of technology in the modern era has fundamentally transformed various sectors, including banking. In the realm of Islamic banking, the integration of digital tools, particularly accounting applications, has become crucial for enhancing transactional efficiency and fostering growth. The study adopts a qualitative approach, utilizing semi-structured interviews with key stakeholders in the Islamic banking sector, including financial managers, IT professionals, and Sharia compliance officers. Document analysis is also employed to review relevant financial reports and compliance documents. The findings reveal that accounting applications are pivotal in automating financial processes, reducing human error, and ensuring that all transactions are compliant with Islamic law. Additionally, these applications contribute to the scalability of Islamic banking operations, support innovation in financial product development, and enhance transparency, all of which are essential for sustainable transaction growth. The study concludes that accounting applications are not merely tools for managing financial transactions but are strategic assets that underpin the growth and development of Islamic banking in the modern era. Through their multifaceted contributions, these applications play a critical role in navigating the complexities of modern finance while adhering to ethical and religious principles, thereby driving the continued expansion and success of Islamic banking.